Economic assessment of flexibility offered by an optimally controlled hybrid heat pump generator: a case study for residential building. (August 2018) - D'Ettorre, F.; De Rosa, M.; Conti, P.; Schito, E.; Testi, D.; Finn, D.P.
Abstract: The ongoing decarbonisation process of the current energy system, driven by the EU directives, requires that more renewable energy sources are integrated in the global energy mix, as well as policies promoting investments in new low-carbon technologies, energy efficiency and grid infrastructure. The technical integration of renewable energy sources into the existing power system is not straightforward, due to the intrinsic aleatory characteristics of renewable production, which make the power grid balance harder. To handle this issue, beside the traditional supply-side management, grid flexibility can also be provided by enabling the active participation of the demand-side in power system operational procedures, by means of the so-called demand-side management (DSM). The present paper is aimed at assessing the ability of a cost-optimal control strategy, based on model predictive control, to activate demand-response (DR) actions in a residential building equipped with a hybrid heat pump generator coupled with a water thermal storage. Hourly electricity prices are considered as external signals from the grid driving the demand response actions. It is shown that the thermal energy storage turns out to be an effective way to improve the controller performances and make the system more flexible and able to provide services to the power grid. A daily cost-saving up to 35% and 15% have been highlighted with a 1 m 3 0.5.m 3 tanks, respectively. Finally, the achievable flexibility is shown to be strictly dependent on the storage capacity and operations, which in turn are affected by the generators sizing.